Islamic values for ICT development with reference to Malaysian context / Aznan Zuhid Saidin - Saidin, Aznan Zuhid (2012)
This study seeks to form an understanding for the incorporation of Islamic values in Information and Communication Technology (ICT) development. ICT development is defined as the activities related to the creation and application of ICT for the purpose of meeting the needs of individuals, organisations, communities, nations and the society at large. The purpose of this study is set upon the backdrop of the need for Muslims ICT practitioners to offer a kind of ICT development that is not void of God-consciousness and Islam as the way of life. Even though previous works have been done on Islamic values and ICT related issues, for example privacy and cybercrime, the fundamental human activities of ICT, namely the communication process, information content creation, and technology shaping, have yet to be discussed in relation to efforts for incorporating Islamic values in ICT development. In other words, with regards to these three human activities, the main questions are what are the issues that needs to be looked into and how to address them in an Islamic manner. The 'how' in this case is treated more in the conceptual sense rather than methodological. Therefore this study approaches ICT development through the three human activities and identifies within the existing literature aspects that provide for the incorporation of Islamic values. For each activity, several points are proposed that reflect the issues that should be given attention and consideration in guiding the effort to incorporate Islamic values in ICT development. In grounding the discussions of this study, a qualitative fieldwork study is conducted to explore the views of Malaysian ICT government officials on incorporating Islamic values in ICT development within the Malaysian context. Findings from this study exemplify issues that requires further studies on this matter. At the end of this study, from what is presented in the discussions, a framework is proposed as a conceptualisation of the incorporation of Islamic values in ICT development. This framework can be used in guiding future studies on ICT and Islamic values. An example is given using the findings from the qualitative study. It is hoped that this study would initiate more efforts to develop information and communication technologies that are Islamicly sound and beneficial to humanity.